Solid State Transformation of TiO2 Rutile and its Photocatalytic Activity - Sulistiyo, Yudi Aris; Kamila, Wilda; Andarini, Novita; Suwardiyanto, Suwardiyanto; Sunnardianto, Gagus Ketut; Haryati, Tanti (Department of Chemistry, Faculty of Mathematics and Natural Sciences, University of Jember, 2022)
Transformation phase TiO2 Rutile was conducted to improve the photocatalytic activity. This study evaluated the transformation phase of TiO2 rutil using solid state rection method and tested for gycerol conversion reaction. a semiconductor material that can be applied for glycerol conversion. The solid state reaction using a mixture of TiO2 Rutile and sodium titanate in mole rasio 1:4 that was heated in 750 oC. XRD analysis evaluated the transformation phase of the solid state reaction product, while band gap energi was calculated following UV-Vis diffuse reflectance data. The photoactivity of glycerol was exposed by UV-Light in various time (5, 10, 15 h) that of the liquid product was analyzed by gas chromatography. Solid state reaction transformed TiO2 rutil to polymorph structure (TiO2 rutile, TiO2 anatase, and sodium titanate Na4O12Ti5). The band gap energy of the product was 3.2 eV. The optimum photocatalytic activity was 62.7% in glycerol concentration 0.25 M for 15 h time reaction.